PENEGAKAN HUKUM TERHADAP PENGGUNAAN SENJATA API RAKITAN DI WILAYAH HUKUM KEPOLISIAN RESOR KOTA PEKANBARU - Yosua Novfryan Nainggolan; Evi Deliana; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
Assembled firearms are also called small arms because they are replicas and are assembled followingthe patterns of standard combat firearms, which are produced by illegal "home-made" gun manufacturingfactories by the public. With the ownership of homemade firearms by civil society, law enforcement must becarried out against anyone who violates the law according to applicable regulations, namely the EmergencyLaw of the Republic of Indonesia Number 12 of 1951. In this case, the Pekanbaru City Police plays the roleof law enforcer. In the 2017-2021 period, cases of the use of homemade firearms are still common, andthere are also cases that have not been resolved. The purpose of writing this thesis, namely; First, knowingthe law enforcement against the use of homemade firearms in the jurisdiction of the Pekanbaru City Police.Second, obstacles in law enforcement against the use of home-made firearms in the jurisdiction of thePekanbaru City Police. Third, efforts to overcome the use of homemade firearms in the jurisdiction of thePekanbaru City Police.This type of research is sociological legal research, namely research that seeks a correlation betweenlaw and society. This research is descriptive, that is, the researcher tries to provide an overview of the casesunder study.The results of this study are that the misuse of homemade firearms still often occurs in the community.The Pekanbaru City Police have implemented preventive and repressive law enforcement, although thereare still internal obstacles such as a lack of information by the police, as well as external obstacles such asa lack of community participation.Keywords : Homemade Firearms – Police – Public